1990
DOI: 10.1111/j.1439-0329.1990.tb01157.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in needle retention associated with the spread and establishment of Phaeocryptopus gaeumannii in planted Douglas fir

Abstract: The needle-infecting fungus Phaeocryptopus gaeumannii (Rohde) Petrak spread to stands of Douglas fir [Pseudotsuga menziesii (Mirb.) Franco] in most parts of New Zealand following its first detection in the central North Island in 1959. At Hanmer Forest in the South Island, the percentage of infected needles rose more rapidly in a provenance from northern inland California than in one from Kaingaroa Forest in the North Island. Increase in infection was accompanied bv a significant decrease in the proportion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…All assessed trees were defi ned as susceptible to the pathogen because of the presence of numerous fruit structures (pseudothecia) detected on needles resulting in yellowing discoloration and an increasing percentage with crown defoliation. During the recent decades, outbreaks of Swiss needle cast have occurred in both native and plantation grown P. menziesii in the Pacifi c Northwest (Hansen et al 2000;Manter et al 2005) and forest plantations in Europe, Turkey (Temel et al 2003), Australia (Marks et al 1989) and New Zealand (Hood et al 1990;Watt et al 2010). According to Hood et al (1990) no provenance is immune to the disease but the provenances from the coastal zones are slower to become infected than provenances from continental sites.…”
Section: Resultsmentioning
confidence: 99%
“…All assessed trees were defi ned as susceptible to the pathogen because of the presence of numerous fruit structures (pseudothecia) detected on needles resulting in yellowing discoloration and an increasing percentage with crown defoliation. During the recent decades, outbreaks of Swiss needle cast have occurred in both native and plantation grown P. menziesii in the Pacifi c Northwest (Hansen et al 2000;Manter et al 2005) and forest plantations in Europe, Turkey (Temel et al 2003), Australia (Marks et al 1989) and New Zealand (Hood et al 1990;Watt et al 2010). According to Hood et al (1990) no provenance is immune to the disease but the provenances from the coastal zones are slower to become infected than provenances from continental sites.…”
Section: Resultsmentioning
confidence: 99%
“…menziesii). However, others (Hood 1982;McDermott and Robinson 1989;Hood et al 1990) have reported inherent differences in incidence of P. gaeumannii infection between interior (P. menziesii var. glauca) and coastal forms of Douglas-fir.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past 60 years, outbreaks of Swiss needle cast in forest plantations have occurred in Europe and the British Isles (Boyce 1940;Peace 1962), the north-eastern USA (Morton and Patton 1970), Turkey (Temel et al 2003), Australia (Marks et al 1982) and New Zealand (Beekhuis 1978;Hood et al 1990). The fungus does not sporulate on dead needles, is not seedborne, and Douglas-fir, including 'bigcone' Douglas-fir (P. macrocarpa) in New Zealand (Gadgil 2005), is its only host ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations